Bibliometric Analysis of English Language Students' Perspectives on Difficulties in Translation - Agusdayanti; Prasetyo, Hazairin Eko; Ismail, Abdul Kadir (English Education Department, 2024)
This study aims to analyze the perspectives of English majors on the difficulties they face in translation using the bibliometric analysis method. This method allows for a quantitative evaluation of academic publications to provide a holistic view of selected research topics over a period of time. Data was collected from the Scopus database, and search results were processed using VOSViewer to generate data visualizations. The analysis results show significant fluctuations in the number of publications related to translation difficulties in recent years, reflecting the ever-changing academic interest in this field. The most frequently discussed topics include translation errors, translation strategies, cultural influences in translation, and the use of technology in translation. Students identified several major difficulties in translation, including linguistic and structural differences between the source and target languages, as well as understanding cultural contexts, which are major obstacles, especially in translating idioms and cultural expressions. Additionally, the lack of knowledge about effective translation techniques is also a significant barrier. This study suggests the need for improvements in the translation education curriculum, the development of more advanced translation tools, and international collaboration between higher education institutions to address translation difficulties. The findings of this study provide a solid foundation for improvements in translation education and the development of more effective strategies to help students overcome translation challenges.